Growth performance and muscle composition response to reduced feeding levels in juvenile red swamp crayfish Procambarus clarkii (Girard, 1852). (17th January 2019) - Jin, Shiyu; Jacquin, Lisa; Ren, Yan; Yu, Jixin; Li, Wei; Lek, Sovan; Liu, Jiashou; Li, Zhongjie; Zhang, Tanglin
Abstract: Overfeeding in aquaculture can lead to suboptimal growth and increased production costs. Red swamp crayfish, Procambarus clarkii, is one of the most noteworthy species cultured in China, but little information is available on the optimal feeding levels of this species, especially in ponds cultured with macrophytes. In this study, we tested the effects of five different feeding levels (20%, 40%, 60%, 80% and 100% satiation) of an artificial diet on growth performance and muscle composition of juvenile P. clarkii in 15 concrete ponds cultured with the macrophyte Hydrilla verticillata (three replicates for each treatment). The results showed that growth performance decreased only when feeding levels were below 60% satiation. Muscle composition analysis revealed that the moisture and ash contents of muscle did not vary significantly with feeding levels but that the lipid and protein contents of muscle significantly decreased when P. clarkii was fed to 40% satiation. Stable isotope analysis suggested a shift in crayfish diets to easily available H. verticillata when feeding levels decreased. With this study, we hope to encourage crayfish farmers to reduce feeding levels and increase natural food items such as macrophytes in cultured ponds to maximize crayfish yields and reduce production costs.